Diskriminasi Pendidikan Masyarakat Terpencil (Equilibrium: Jurnal Pendidikan, 2019)
The research entitled "Discrimination in remote community education (Case study of Buntu Mondong village in Buntu Batu District, Enrekang District" aims to determine the existence of education discrimination in remote communities in Buntu Mondong village, Buntu Batu District, Enrekang District, with qualitative research methods. This research was conducted by observing the condition of the school which includes the condition of students, teachers and infrastructure as well as the conditions in the surrounding environment which also influence the quality of education.The data has been collected, then analyzed descriptively.The results of the study illustrate the occurrence of educational discrimination in the Gura SDN NO. educators and infrastructure facilities that cause education in the area to be not optimal.The available educators lack excellence in midwives and have low quality so that what is given to their students is also mediocre. a Less quality educator, Infrastructure that supports the learning process teaches very little, so the learning process often experiences obstacles. By that, especially for the government and education implementers should increase attention to education in remote areas, especially in SDN NO 79 Gura. Keywords: Discrimination, Education, Remote Communities